EFL Learners’ Translation Strategies: A Semantic Bridge in Two Languages - Jupri, Jupri; Rahman, Arif; Hassan, Ahmad Javed; Manu, Said Malika Tridane (JOLLT Journal of Languages and Language Teaching, 2024)
This study examines translation strategies and the impact of translation strategies on translated texts produced by master’s students of the English program at the campus of UNDIKMA Mataram. This study used a qualitative approach that included recording methods, specifically internal data recording. The data collected were 10 products translated from English to Indonesian by the requester.Â The English translation includes 390 words.Â They are allowed to use traditional or offline/electronic dictionaries when translating text. The study used several translation strategies, which are translation methods (literal translation and oblique translation) and translation processes (borrowing, calque translation, literal translation, modulation, transposition, equivalence, and translation).Â Transform).Â The results show that master’s students tend to use local strategies and literal translation methods in translation.Â This affects the quality of the translation, making it less natural in the target language.Â In addition, translation errors also occur due to wrong/incorrect word selection, leading to failure to convey the message in the text source. The result of this research expected will bring valuable contributions to future research and courses serving translation activities.